Molecular characterization of the genes encoding DNA gyrase and topoisomerase IV of Listeria monocytogenes - Lampidis, Robert; Kostrewa, Dirk; Hof, Herbert (The journal of antimicrobial chemotherapy, 2002)
The genes encoding subunits A and B of DNA gyrase and subunits C and E of topoisomerase IV of Listeria monocytogenes, gyrA, gyrB, parC and parE, respectively, were cloned and sequenced. Compared with the sequences of quinolone-susceptible bacteria, such as Escherichia coli and Bacillus subtilis, the quinolone resistance-determining region (QRDR) of DNA gyrase subunit A was altered; the deduced amino acid sequences revealed the substitutions Ser-84→Thr and Asp/Glu-88→Phe, two amino acid variations at hot spots, commonly associated with resistance to quinolones. No relevant divergences from QRDR consensus sequences were observed in GyrB or both topoisomerase IV subunits. Thus, it could be argued that the amino acid substitutions in GyrA would explain the intrinsic resistance of L. monocytogenes to nalidixic acid. In order to analyse the actual role of the GyrA alterations, a plasmid-encoded gyrA allele was mutated and transformed into L. monocytogenes. However, these heterodiploid strains were not affected in their resistance to nalidixic acid. The effects of the mutant plasmids on ciprofloxacin and sparfloxacin susceptibility were only modest.
Gesehen am 07.04.2022